Ultrahigh-Speed Imaging of Rotational Diffusion on a Lipid Bilayer - Mazaheri, Mahdi; Ehrig, Jens; Shkarin, Alexey; Zaburdaev, Vasily; Sandoghdar, Vahid (Nano Letters, 2020)
We studied the rotational and translational diffusion of a single gold nanorod linked to a supported lipid bilayer with ultrahigh temporal resolution of two microseconds. By using a home-built polarization-sensitive dark-field microscope, we recorded particle trajectories with lateral precision of 3 nm and rotational precision of 4°. The large number of trajectory points in our measurements allows us to characterize the statistics of rotational diffusion with unprecedented detail. Our data show apparent signatures of anomalous diffusion such as sublinear scaling of the mean-squared angular displacement and negative values of angular correlation function at small lag times. However, a careful analysis reveals that these effects stem from the residual noise contributions and confirms normal diffusion. Our experimental approach and observations can be extended to investigate diffusive processes of anisotropic nanoparticles in other fundamental systems such as cellular membranes or other two-dimensional fluids.
CRIS-Team Scopus Importer:2020-10-30
Keywords: anomalous diffusion; dark-field microscopy; nanorod; rotational diffusion; scattering; single particle tracking